Personalized Therapy Using Drug Delivery Devices - Kazi Kutubuddin (Emerging Trends in Personalized Medicines, 2026)
The persistent challenge in modern medicine lies in inter-patient heterogeneity, rendering standardized drug dosing protocols suboptimal for many chronic conditions. Traditional pharmacokinetics fail to account for real-time biological fluctuations, leading to cycles of ineffective treatment or dose-limiting toxicity. This paper explores the critical intersection of advanced drug delivery devices (DDDs) and personalized medicine, positioning these technologies as the vital link translating genomic and biological data into tangible, patient- specific interventions. We study DDDs that move beyond simple sustained release, focusing instead on closed-loop systems incorporating sophisticated biosensors, dynamic reservoir control, and predictive algorithms. Technologies discussed include micro-osmotic pumps, smart polymer implants, and remotely controlled microneedle patches—all capable of adjusting drug release kinetics instantaneously based on biomarkers (e.g., glucose levels, inflammatory markers, or drug concentration). The implementation of such personalized drug delivery heralds the shift toward autonomic pharmacology, where the therapeutic system—rather than the patient or clinician—manages complex dosing schedules. While significant hurdles remain concerning biocompatibility, regulatory approval, and data security, the promise of eradicating the one-size- fits-all model through precision engineering represents the next major paradigm shift in therapeutic efficacy and patient adherence.
Keywords: Implantable devices; Personalized Therapy; Personalized medicine; Wearable devices; drug delivery dev; ices (DDDs)